(untitled) (Research, Society and Development, 2021)
The new classification of periodontal and peri-implant diseases and conditions published in 2018 includes gum pathologies and diseases not induced by biofilm, including drug-related gingival pigmentations. Chloroquine and hydroxychloroquine have been used for years due to their immunosuppressive and anti-inflammatory effects and are now the target of studies on possible efficacy against the new coronavirus (SARS-CoV-2). This study aims to identify the case reports of oral pigmentation related to chronic use of chloroquine and hydroxychloroquine. A survey of scientific articles was carried out, using the terms hyperpigmentation, chloroquine, hydroxychloroquine as descriptors, in the databases: Google scholar, SciElo, PubMed, Medline and LILACS. Twelve case report and case series studies were selected with 18 clinical cases within the scope of this study. These were evaluated taking into account the characteristics of hyperpigmentation, medication used, reason and time of use, in addition to the patient’s age and sex. Of the 18 cases analyzed, 15 were found on the hard palate. In addition, pigmentations were more prevalent in females and had a bluish-gray or bluish-black color. Therefore, it is crucial that the dental surgeon is attentive to make the differential diagnosis with other lesions that have the potential for malignancy.